Autistic Spectrum Disorders: from Theory to Practice - Minaidou, Despo (My University, 2026)
Held in Nicosia presented by Dr. Rita R. Jordan, BSc. MSc. MA., PhD., C.Psychol. OBE, Emeritus Professor in Autism Studies: Autism Centre for Education & Research, the University of Birmingham, UK.